Word Formation Analysis of English Slang Words in Ant-Man and The Wasp Movie - Verdi Firdaus; Havid Ardi (Universitas Negeri Padang, 2023)
This study aimed to determine the frequency of slang words in the film Ant-Man and The Wasp, as well as the word formation processes of slang words. This study was descriptive qualitative. This study employed George Yule's theory of word formation processes (2010). The researcher identified seven types of word formation in the slang words of the Ant-man and The Wasp script: blending, borrowing, clipping, multiple-process, compounding, conversion, and coinage. The data was collected from slang words found in the script of the movie. This study indicated that clipping was the most frequent form of word formation, representing for 29.60% of all occurrences. It was followed by coinage and blending, each representing for 22.53% of the total. It was then followed by compounding and borrowing at the same rate of 8.45%, as well as conversion at the rate of 7.04%. With a mere 1.40 percent as a result, multiple-process is the least frequent.